Geo-Congress 2019. selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering, March 24-27, 2019, Philadelphia, Pennsylvania - Meehan, Christopher L.; Kumar, Sanjeev, 1964-; Pando, Miguel Angel, 1968-; Coe, Joseph T. (American Society of Civil Engineers, 2019)
Selected papers from sessions of the Eighth International Conference on Case Histories in Geotechnical Engineering, held in Philadelphia, Pennsylvania, March 24-27, 2019. Sponsored by the Geo-Institute of ASCE. This Geotechnical Special Publication contains 35 peer-reviewed papers on earth retaining structures and geosynthetics. Topics include: deep excavations and support systems; top-down and bottom-up construction; monitoring and assessment of earth retaining structures; geosynthetic materials and properties; and case studies. GSP 306 will provide practitioners, academics, and policymakers a valuable reference on geosynthetics and earth retaining structures.
Keywords: Geotechnical engineering -- Congresses.; Geotechnical engineering -- Case studies.; Retaining walls -- Congresses.; Geosynthetics -- Congresses.; Retaining walls -- Case studies.; Geosynthetics -- Case studies.; elektronické knihy; electronic books